Iran’s counter-hegemony under the leadership of Mahmoud Ahmadinejad (2005-2009) towards US hegemony in West Asian region - Riki Rahman; Zarina @ Zairina Othman; Kamaruzaman Yusoff; Ruhanas Harun (Institut Kajian Rantau Asia Barat, 2013)
Since the dissolution of Soviet Union in 1991, United States of America (USA) expands its hegemonic power around the world, including oil-rich West Asia of which USA’s interest in this region is the oil resources. USA’s oil reserve decreased in the last few years but its consumption in transportation, industrial, residential and commercial, and electric power increased. USA needs oil supply from other regions especially the West Asia and Iran because oil resources in this region are more abundant than other regions. However, USA’s effort to tighten its hegemony in West Asia faced great challenge from Iran’s anti-USA policy since 1979. This article analyzes those counter-hegemony strategies used by Iran, under Mahmoud Ahmadinejad for the first term of his leadership (2005-2009), against USA’s hegemonic expansion in this region. This study uses descriptive and analytical qualitative approach to understand and evaluate those strategies used by Ahmadinejad. By using counter-hegemony theory as a tool of analysis, this study found that Iran, under Ahmadinejad's leadership, employs war of position against USA hegemony. This study also found that Iran’s counter-hegemony efforts are a form of balance of power against USA in the West Asia region.